Leaf Epicuticular Waxes of the Eceriferum Mutants in Arabidopsis. - Jenks, M. A. (1995)
Wild-type Arabidopsis leaf epicuticular wax (EW) occurs as a smooth layer over the epidermal surface, whereas stem EW has a crystalline microstructure. Wild-type EW load was more than 10-fold lower on leaves than on stems. Compared with the EW on wild-type stems, EW on wild-type leaves had a much higher proportion of their total EW load in the form of alkanes and 1-alcohols; a large reduction in secondary alcohols, ketones, and esters; and a chain-length distribution for major EW classes that was skewed toward longer lengths. The eceriferum (cer) mutations often differentially affected leaf and stem EW chemical compositions. For example, the cer2 mutant EW phenotype was expressed on the stem but not on the leaf. Compared to wild type, the amount of primary alcohols on cer9 mutants was reduced on leaves but elevated on stems, whereas an opposite differential effect for primary alcohols was observed on cer16 leaves and stems. Putative functions for CER gene products are discussed. The CER4 and CER6 gene products may be involved in fatty aldehyde reduction and C26 fatty acylcoenzyme A elongation, respectively. CER1, CER8, CER9, and CER16 gene products may be involved in EW substrate transfer. The CER3 gene product may be involved in release of fatty acids from elongase complexes. CER2 gene product may have regulatory functions.